2018
DOI: 10.15171/icnj.2018.12
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Effectiveness of the Mindfulness-Based Cognitive Therapy and the Metacognition Treatment on Anxiety, Depression and Stress Among Breast Cancer Patients

Abstract: Background: The present study aimed to compare the effectiveness the metacognition treatment (MCT) and mindfulness-based cognitive therapy (MBCT) on anxiety, depression, and stress in the females with breast cancer. Methods: The planning of this study is through a quasi-experimental method of pretest and posttest type with control group. The target society of the research included every cancer patient who admitted to Tehran hospitals for breast cancer. Through assigned randomly, 12 patients were selected for t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 22 publications
1
9
0
Order By: Relevance
“…Among the 18 studies, eight studies showed improvement in mental health outcomes [ 10 , 20 – 22 , 24 , 27 , 29 , 34 ]. Specifically, psychoeducation [ 22 ] and CBT [ 27 ] improved depression and anxiety symptoms and stress. Mindfulness-based cognitive therapy had a significant long-term effect ( p = 0.014) on self-management, posttraumatic growth, and functional disability [ 29 ].…”
Section: Resultsmentioning
confidence: 99%
“…Among the 18 studies, eight studies showed improvement in mental health outcomes [ 10 , 20 – 22 , 24 , 27 , 29 , 34 ]. Specifically, psychoeducation [ 22 ] and CBT [ 27 ] improved depression and anxiety symptoms and stress. Mindfulness-based cognitive therapy had a significant long-term effect ( p = 0.014) on self-management, posttraumatic growth, and functional disability [ 29 ].…”
Section: Resultsmentioning
confidence: 99%
“…The reviewed studies are also informative in building a base for the effectiveness of psychotherapeutic techniques in the psycho-oncologic treatment of Muslim patients. This review con rms the positive outcomes of various psychotherapeutic interventions on improving mental health, such as improving symptoms of depression and anxiety and stress [10,17,18,19,21,24,26,31]. Consulting sessions [19,21] provide patients with practical and educational information and resources that are related to emotions such as depression, anxiety, and fear associated with cancer.…”
Section: Discussionmentioning
confidence: 94%
“…Consulting sessions [19,21] provide patients with practical and educational information and resources that are related to emotions such as depression, anxiety, and fear associated with cancer. Mindfulness-based cognitive therapy [24,26] increases patients' awareness of their feelings; throughout this therapy, patients acquire cognitive skills that promote metacognitive awareness, acceptance of negative thoughts, and an ability to effectively cope with psychological distress. Aromatherapy [18] entails using volatile essential oils of plants to enhance mental health.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations